Persistence of commuting habits: Context effects in Germany - Ramona Jost (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2020)
Based on the geo-referenced data, I analyse the commuting behaviour of employees in Germany. With the help of a behavioural economic approach, which is based on the investigation of Simonsohn (2006) for the US, I can show that it is not only the wage and the individual heterogeneity that shape commuting decisions. Instead, the commuting behaviour depends on the context individuals observe in the past. In particular, I demonstrate that the commuting behaviour is influenced by past-observed commutes: Worker choose longer commuting times in a region they just moved to, the longer the average commute was in the region they moved away. This effect applies especially for older employees, but is the same for men and women. Moreover, my robustness checks indicate that individual heterogeneity, selectivity or endogeneity issues do not drive this effect. In addition, I show if individuals stay in the new region, the effect of the previous region disappears, as workers adapt the commuting behaviour of the new region and move again within the new region. This is consistent with the prediction of behavioural economic theory, but refuses the assumption of stable taste differences. – – Das vorliegende Papier analysiert auf der Grundlage der georeferenzierten Daten das Pendelverhalten der Beschäftigten in Deutschland. Mit Hilfe eines verhaltensökonomischen Ansatzes, der auf der Studie von Simonsohn (2006) für die USA basiert, kann ich zeigen, dass nicht nur der Lohn und die individuelle Heterogenität die Pendelentscheidung prägen, vielmehr hängt das Pendelverhalten vom Kontext ab, den die Individuen in der Vergangenheit ausgesetzt waren. Insbesondere wird das Pendelverhalten von den in der Vergangenheit beobachteten Pendelzeiten beeinflusst: Beschäftigte entscheiden sich, nach einem Umzug, in eine neue Region, für einen längeren Pendelweg je länger die durchschnittliche Pendelzeit in der Region vor dem Umzug war. Dieser Effekt ist besonders hoch für ältere Beschäftigte, jedoch fällt er für Männer und Frauen gleich stark aus. Meine Ergebnisse sind robust und zeigen, dass weder individuelle Heterogenität noch Selektivität und Endogenitätsprobleme meine Ergebnisse treiben. Zudem verschwindet der Effekt der Region vor dem Umzug, falls Beschäftigte in der neuen Region wohnen bleiben: Beschäftigte ziehen erneut um und passen sich dem Pendelverhalten der neuen Region an. Dies steht im Einklang mit den Vorhersagen der verhaltensökonomischen Theorie, nicht allerdings mit den Annahmen konstanter Präferenzen.
Keywords: J60; R10; R19; R23; 330; Commuting; behavioural economic; context effects; movers; geo-referenced data; commuting decision